2012
DOI: 10.5539/ass.v8n14p91
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Peer Learning: Student to Student, Lecturer to Lecturer

Abstract: This article explores how lecturers in statistics have adopted a model for a student peer learning project initially established in a music school. The exploration shows how disciplinary differences generate different peer learning approaches between students and how a team of lecturers has adapted a project from one discipline and institution to another. In essence, it explores the nature of peer learning from the perspective of student peers, including the extra insight that is available from the view of lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…One factor affecting expertise development is the range of people accompanying experts during their careers. Research has revealed that the acquisition of expertise is related to the individual’s social background (Moore, Burland, & Davidson, 2003; Petocz, Duke, Bilgin, & Reid, 2012; Sichivitsa, 2007; Sloboda, 2000) in terms of motivation, practice habits and learning. Krampe and Ericsson (1995) acknowledged that deliberate practice is not necessarily intrinsically motivating or enjoyable for the individual.…”
mentioning
confidence: 99%
“…One factor affecting expertise development is the range of people accompanying experts during their careers. Research has revealed that the acquisition of expertise is related to the individual’s social background (Moore, Burland, & Davidson, 2003; Petocz, Duke, Bilgin, & Reid, 2012; Sichivitsa, 2007; Sloboda, 2000) in terms of motivation, practice habits and learning. Krampe and Ericsson (1995) acknowledged that deliberate practice is not necessarily intrinsically motivating or enjoyable for the individual.…”
mentioning
confidence: 99%
“…As a result group members increased research outputs. The design of this collaborative practice draws from peer support and cooperative learning models (see Petocz et al 2012;Topping 2005) and models of peerteaching, which facilitate and promote the improvement of communication skills and encourage independent learning (see Lim 2014).…”
Section: Writing Groups As Collaborative Practicementioning
confidence: 99%
“…This fact is indicated through a classroom interaction, where the interaction input, process, and output are positively well-resulted performed. Petocz et al (2012) rely on this situation with the learning opportunities, such as lectures, tutorials, rehearsals and classroom discussion forum. A well-managed classroom will be the priority, where the productive interaction is encouraged (Wrench, Richmond & Gorham, 2009).…”
Section: A Influencing Factors Of Divergent Approachmentioning
confidence: 99%